Adhesive wear behavior of gas tungsten arc welded FeB-FeMo-C coatings - Yaz, Mehmet (Walter de Gruyter Gmbh, 2022)
In this article, a gas tungsten arc welding is used as a high energy density beam to form a surface over 0.15% carbon steel with FeB, FeMo, and graphite powders. The microstructure, microhardness, and dry-sliding wear behavior of the composite coating were investigated using optical micrography, X-ray diffraction, scanning electron microscopy, and energy-dispersive X-ray spectrometry. Microstructural investigations reveal that FeB-reinforced coating exhibited a homogeneous microstructure that consists of dendrites and eutectic. A lot of types of carbide and borides were formed. MoB4, Fe2MoC, B8C, Mo2BC, MoB, Fe3Mo, Fe3B, B25C, Fe7C3, FeB, Mo2B5, and MoC were seen in coated surfaces. Graphite iron boride coatings obtained by the gas tungsten arc welding process improved the wear resistance of carbon steel.
Keywords: adhesive wear; coating; FeB; FeMo; gas tungsten arc welding